2020
DOI: 10.37616/2212-5043.1059
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Off-Hour Presentations And In-Hospital Mortality For Patients With Acute ST-Elevation Myocardial Infarction Treated With Primary Percutaneous Coronary Intervention

Abstract: Objectives This study aimed to assess the effect of the admission time (on-hours versus off-hours) on in-hospital mortality in patients with ST-elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention (PPCI) in a region without STEMI network. Methods We analysed in-hospital the mortality among 300 consecutive ST-segment elevation myocardial infarction (STEMI) patients treated with PPCI between March 2012 and February 2017. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The majority of studies included in this meta-analysis were performed in developed countries, of which the STEMI network of each developed country probably allows a timely primary PCI that contributes to similar mortality risk between the two admission times. In fact, several studies from developing countries 6 9 25 35 45 47 52 58 also found a similar early mortality risk between two admission times.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The majority of studies included in this meta-analysis were performed in developed countries, of which the STEMI network of each developed country probably allows a timely primary PCI that contributes to similar mortality risk between the two admission times. In fact, several studies from developing countries 6 9 25 35 45 47 52 58 also found a similar early mortality risk between two admission times.…”
Section: Discussionmentioning
confidence: 72%
“…A total of 384,452 patients from 56 studies were included. 2 3 4 5 6 7 8 9 10 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Baseline characteristics are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Early reperfusion, usually through percutaneous coronary intervention (PCI), was a primary factor in the prognosis and clinical outcome of AMI. [ 40 , 41 ] Severe neointimal proliferation and hyperplasia, vascular remodeling, increased vascular smooth muscle cell proliferation and migration, and chronic inflammation after the coronary stent implantation procedure are the main causes of restenosis. [ 10 ] MiR-208 had a higher AUC value in healthy controls and patients with acute chest pain and the mixed population.…”
Section: Discussionmentioning
confidence: 99%